2018
DOI: 10.12669/pjms.343.14893
|View full text |Cite
|
Sign up to set email alerts
|

Ileosigmoid knotting: One of the largest single-center series

Abstract: Ileosigmoid knotting (ISK) is the wrapping of the ileum or sigmoid colon around the base of the other structure, causing a double-loop intestinal obstruction. The disease generally presents as an intestinal obstruction with volvulus triad, including abdominal pain/tenderness, distention, and obstipation. Abdominal X-ray findings are not pathognomonic, and computerized tomography (CT) and magnetic resonance imaging (MRI) are more useful in the diagnosis. A patient with ISK generally requires an emergency laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 14 publications
4
62
1
Order By: Relevance
“…The reported mortality from ISK varies from 0% to 48% [5]. Higher mortality has been observed in patients with old age (<60 years), delayed presentation (>24 hours), and the presence of gangrenous bowel [3]. Considering the presence of the above high-risk factors in our patient along with bowel edema and luminal discrepancy, resection of the gangrenous segments with end ileostomy and Hartmann's procedure was performed in this case.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The reported mortality from ISK varies from 0% to 48% [5]. Higher mortality has been observed in patients with old age (<60 years), delayed presentation (>24 hours), and the presence of gangrenous bowel [3]. Considering the presence of the above high-risk factors in our patient along with bowel edema and luminal discrepancy, resection of the gangrenous segments with end ileostomy and Hartmann's procedure was performed in this case.…”
Section: Discussionmentioning
confidence: 81%
“…ISK is one of the uncommon but potentially life-threatening causes of bowel obstruction, in which a portion of the ileum and sigmoid colon wrap around each other, forming a closed-loop obstruction. It is commonly seen in the Africa, Asia, and the Middle East populations, with a male preponderance and mean age of presentation around 40 years [2,3]. Endemicity of the disease has also been reported in Turkey, specifically in Eastern Anatolia.…”
Section: Discussionmentioning
confidence: 99%
“…Our case of ISK in a young man with Down's syndrome makes for a rare diagnosis. Atamanalp [ 4 ] suggested that high altitude, high-fiber diet habits, male gender and advanced age are known as probable causes of an anatomical predisposition to ISK, namely, an elongated sigmoid colon with a narrow mesentery in addition to a hypermobile terminal ileum. In our case, we can suggest the presence of congenital mega-colon which is part of the malformations of the digestive tract in Down's syndrome as an anatomical cause of ISK [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis is difficult because of its rarity and clinico-radiological atypia, it is possible in less than 20% of cases [ 3 ]. Abdominal pain is constant, often sub-acute and progressive, associated with obstipation (98.8-100%), abdominal distension (94-100%), nausea and vomiting (77.5-100%) and rebound tenderness (36.8-100%) [ 4 , 6 , 7 ]. Abdominal X-ray may show disproportionate distension with large air-fluid levels in the sigmoid colon occupying the right side of the abdomen, with multiple air-fluid levels of the small intestine on the left side of the abdomen [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Turkey, particularly our region, Eastern Anatolia, is endemic for SV and ISK 1-4. The plausible causes of this interesting dispersion include a diet high in fibre and vegetables and the high altitude, which cause a redundant sigmoid colon with a narrow mesentery, an anatomical feature that is known to be a predisposing factor for SV and ISK 8-10. As a result of our comprehensive experience with SV and ISK, our clinic has produced many publications on these topics over the years.…”
Section: Discussionmentioning
confidence: 99%